The teenagers’ idea about the prevention of crack - Magalhães, Juliana Macêdo; Monteiro, Claudete Ferreira de Souza; Figueiredo, Maria do Livramento Fortes (Revista de Pesquisa Cuidado é Fundamental Online, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 10.0pt; line-height: 150%; font-family: "Trebuchet MS","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Objectives: <span style="font-size: 10.0pt; line-height: 150%; font-family: "Trebuchet MS","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">To describe and understand ideas of adolescents on the crack use prevention. Methods: A qualitative study with the action research method was conducted, located at the Family Health Strategy, a community located in the state of Maranhao. The subjects were eleven adolescents. The data were collected by means of seminars and analyzed using content analysis. Results: It was observed that adolescents have the conception that the use of crack can be triggered by a lack of information. They feel the need to be more prepared in order to better understand the possible ways of prevention, complications and risks resulting from crack abuse. Conclusion: It is concluded that the professionals of the Family Health Strategy need to be more prepared when it comes to adolescents, so they can actually recognize the real needs of these individuals. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>